The Anatolian Journal of Cardiology 2021
DOI: 10.5152/anatoljcardiol.2021.33232
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between frontal QRS-T duration and the severity of coronary artery disease in who were non-diabetic and had stable angina pectoris

Abstract: Objective: There is a known relationship between frontal-QRS-T (F-QRS-T) angle and coronary artery disease (CAD). This study examined the relationship between F-QRS-T angle changes and CAD severity in patients with stable CAD. Methods: A total of 202 patients were included in the study after the implementation of exclusion criteria among 894 patients, who were admitted to the outpatient clinic with stable angina pectoris between September 2018 and September 2019. The F-QRS-T angle calculated on the 12-lead ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Frontal QRS-T angle was found to be associated with all-cause death, cardiac death, and arrhythmias in patients with ischemic heart failure, non-ischemic heart failure, heart failure with preserved ejection fraction, myocarditis, acute myocardial infarction, and in the normal population [ 2 , 3 - 11 ]. In addition, patients with the coronary slow-flow [ 14 ] and severe coronary artery disease [ 15 ] were found to have wider frontal QRS-T angles compared to those without. In our study, the frontal QRS-T angle was observed to be wider in the mortality group.…”
Section: Discussionmentioning
confidence: 99%
“…Frontal QRS-T angle was found to be associated with all-cause death, cardiac death, and arrhythmias in patients with ischemic heart failure, non-ischemic heart failure, heart failure with preserved ejection fraction, myocarditis, acute myocardial infarction, and in the normal population [ 2 , 3 - 11 ]. In addition, patients with the coronary slow-flow [ 14 ] and severe coronary artery disease [ 15 ] were found to have wider frontal QRS-T angles compared to those without. In our study, the frontal QRS-T angle was observed to be wider in the mortality group.…”
Section: Discussionmentioning
confidence: 99%
“…This parameter is not routinely used since advanced knowledge is required for its determination and analysis. Recent studies have demonstrated that FQRST enlargement is associated with the aging process [6], the risk of cardiac arrhythmias, such as atrial fibrillation [7], hypertension [8], the severity of coronary artery disease and myocardial infarction [9,10], heart failure [11], idiopathic dilated cardiomyopathy [12], etc. It is also recommended for stratifying cardiac risk [13] and for monitoring patients after cardiac resynchronization therapy [14], myocardial revascularization, or cardiac valve surgery [15].…”
Section: Introduction 1the Frontal Qrs-t Angle On Ecg In Epidemiologi...mentioning
confidence: 99%